Occurrence of New Diseases of Casuarina equisetifolia in India - Mohanan, C.; Sharma, J. K. (Indian Forester, 1989)
Diseases of Casurina equisetifolia in nurseries and trial plantations in southern states of India are reported. Rhizoctonia solani causing seedling blight, stem canker and root rot (nurseries) and branch canker and foliage infection caused by Phomopsis casuarinae, pink disease caused by Corticium salmonicolor (trial plantation) are new record from India. Application of Vitavax (0.05% a.i.) in nurseries effectively controlled the diseases caused by R. solani.